Issues of Single Mothers in Practice Parenting Style to Adolescent in Indonesia - Hamzah, Ika Indrawaty; Jaafar , Fauziah Md (South Asian Journal of Social Sciences and Humanities, 2020)
This paper aims to illustrate the issues of single mothers in practice parenting style to adolescents in Indonesia. Single mothers are a massive challenge to continue living with their children because they carry out multiple responsibilities, including childcare and the livelihood of their children. However, they have lost their dependence, inability to give birth to young children and in school using heavy stress including financial, psychological, stigma, social, and social problems in educating their children. To overcome the problems faced, single mothers need social support from the parties concerned. Therefore, this paper recommends to the relevant parties for each program that can assist single mothers who can be independent and various problems faced that squeeze life with their children.